Social responsibility of business and government in the conditions of the COVID-19 pandemic - George Abuselidze; Anna Slobodianyk (E3S Web of Conferences, 2020)
The paper has proved that socially responsible activities of enterprises in the current conditions are considered as an example of solidarity of business and the society in terms of contributing on improving the living standards of the population, in particular, to ensure decent conditions and remuneration, enhancing health care, reducing negative impacts on the environment. The article analyses the fact that due to the spread of COVID-19, businesses around the world are counting losses, and governments are developing anti-crisis measures for national economies. However, in a country with small open economies, a new significant expansion of the set of measures to the existing list can lead to the loss of millions of jobs and significant losses of budgets at various levels. It has been proven that entrepreneurs are responsible for the well-being of millions of employees and are also looking for possible ways to prevent the shutdown of enterprises, to avoid more complex consequences in order not to leave a significant part of the population without the means of subsistence. Therefore, for small open economies in a system of such methods, it is important to focus on the synergetic effect of the implementation of the socially responsible relationship of business, government, and individuals in the period of introduction of quarantine measures and dissemination practices for the implementation of socially responsible activities on macro and micro level which will get a positive result and minimize job loss of millions of people.
Keywords: H55; L31; M14; Z13; 330; Socially Responsible Business; Social Entrepreneurship; CSR; Quarantine measures; Pandeconomy; Covid-19